Inter-annual variability in Chinstrap penguin diet at South Shetland and South Orkneys Islands - Rombola, Emilce Florencia; Marschoff, Enrique Ricardo; Coria, Néstor Rubén (Polar Biology)
Inter-annual variability in the diet of Chinstrap penguins (Pygoscelis antarctica) at Laurie Island (South Orkney Islands) and 25 de Mayo/King George and Nelson Islands (South Shetland) was examined based on stomach contents of adults during the 2002/2003-2006/2007 and 2002/2003-2004/2005 breeding seasons, respectively. Krill (Euphausia superba) dominated the diet as frequency of occurrence (in 100% of samples), number (>99%), and percentage contribution in weight (>94.8%). Other prey items were minor and varied between years. The weight of stomach contents was significantly different. The percentage in weight of whole krill was used to compare the feeding conditions across seasons. It differed significantly at the three sites studied. Distribution of krill size varied among years and localities, showing different krill availability for penguins. © 2009 Springer-Verlag. Fil: Rombola, Emilce Florencia. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Marschoff, Enrique Ricardo. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Coria, Néstor Rubén. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina